2008
DOI: 10.1111/j.1744-1609.2008.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions that assist caregivers to support people with dementia living in the community: a systematic review

Abstract: Objectives  The objective of this review was to assess the effectiveness of interventions that assist caregivers to provide support for people living with dementia in the community. Inclusion criteria  Types of participants  Adult caregivers who provide support for people with dementia living in the community (non-institutional care). Types of interventions  Interventions designed to support caregivers in their role such as skills training, education to assist in caring for a person living with dementia and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
140
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 48 publications
5
140
1
2
Order By: Relevance
“…For effectiveness indicators, we examined various factors affecting a caregiver and analyzed existing studies on support groups for caregivers of demented patients. Using classifications developed by previous studies, including Brodaty et al (2003), Cooke et al (2001), Nelis et al (2007), Parker et al (2008), Pusey and Richards (2001), and Schulz et al (2002), the assessment indicators for support groups focused on the main caregiver's psychological well-being, depression, burden, and social outcome variables.…”
Section: Introductionmentioning
confidence: 99%
“…For effectiveness indicators, we examined various factors affecting a caregiver and analyzed existing studies on support groups for caregivers of demented patients. Using classifications developed by previous studies, including Brodaty et al (2003), Cooke et al (2001), Nelis et al (2007), Parker et al (2008), Pusey and Richards (2001), and Schulz et al (2002), the assessment indicators for support groups focused on the main caregiver's psychological well-being, depression, burden, and social outcome variables.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of care for persons with dementia has shifted from the sick person to family-oriented care, with family members being partners in care. There is a growing amount of empirical evidence supporting that some intervention strategies have a beneficial impact on the burden of family caregivers [62]. For example, a training program for caregiving skills has been found to be relatively more effective in reducing family distress and strengthening care management [63,64].…”
Section: Family Interventionsmentioning
confidence: 99%
“…Multicomponent interventions resulted in statistically significant effects in improving self-efficacy, depression, subjective well-being and perceptions of burden. Noneffective interventions that should be avoided included only referring caregivers to support groups, only providing self-help materials and only offering peer support [62]. …”
Section: Family Interventionsmentioning
confidence: 99%
“…A positive relationship between self-efficacy and caregiver HRQoL has also been identified [11,25]. The results of intervention studies have found that enhancing caregiver self-efficacy significantly improved these caregivers' mental and physical health outcomes [26,27,28,29]. According to Bandura [24], people's self-efficacy for a specific behavior is influenced by external factors.…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy is defined as ‘the belief in one's capabilities to organize and execute the course of action required to produce given attainments' [24]. An increasing number of studies have reported on the significant association between caregiver self-efficacy and health-related outcomes [11,18,25,26,27,28,29]. Studies on caregiver self-efficacy have found significantly lower levels of self-efficacy in caregivers who are dealing with relatives with dementia than in caregivers dealing with relatives with other diseases [18].…”
Section: Introductionmentioning
confidence: 99%